Bilateral inguinal bladder hernias. Issue 7 (18th July 2022) - Fujita, Naoya; Ono, Yosuke; Obuchi, Yasuhiro; Tanaka, Yuji
Abstract: Inguinal hernia may contain the bladder as one of its contents, while bilateral inguinal bladder herniation is rare. Urinary obstruction and obesity are associated with increased abdominal pressure and are risk factors of bladder herniation. Clinicians should be aware of the bladder hernia in elderly with chronic dysuria and obesity. Abstract : Clinicians should be aware of the bladder hernia in elderly with chronic dysuria and obesity.